CREATING A PROTOTYPE OF AN INTERACTIVE LEARNING GAME IN MOLECULAR AND CELL BIOLOGY - Koka, Rudīte; Šķipars, Vilnis; Šukele, Renāte; Kroiča, Juta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
At the beginning of medical studies at Rīga Stradiņš University (RSU), students’ knowledge and skills differ widely. In the first semester, students must take a course, “Molecular and Cell Biology.” In many cases, problems in students’ abilities to absorb new information of this new, specific nature are evident. The reason for this is insufficient prior preparation. On average, 3-4 % of students failed this course each academic year. After focus group discussions and interviews with colleagues and leading specialists in information technologies, we concluded the need to create an interactive and pedagogically correct tool for improving students` competence in molecular and cell biology; one such tool could be an interactive learning game. This article describes the process of creating a learning game prototype in molecular and cellular biology. With the help of selected RSU students, a prototype was created. The involvement of students proved beneficial for them (improving understanding of the topics) and for us (clarifying students’ preferences for the game’s design).The learning game was tested with a target group (1st-semester students from the Medicine and Dentistry faculties of RSU). Initial feedback from the students and teachers certifies that this example is an opportunity to provide a desired, low-stress self-paced learning resource.